An Architectural Approach to the Design and Analysis of Cyber-Physical Systems - Rajhans, Akshay; Cheng, Shang-Wen; Schmerl, Bradley; Garlan, David; Krogh, Bruce; Agbi, Clarence; Bhave, Ajinkya (Electronic Communications of the EASST, 2009)
This paper presents an extension of existing software architecture tools to model physical systems, their interconnections, and the interactions between physical and cyber components. A new CPS architectural style is introduced to support the principled design and evaluation of alternative architectures for cyber-physical systems (CPSs). The implementation of the CPS architectural style in AcmeStudio includes behavioral annotations on components and connectors using either finite state processes (FSP) or linear hybrid automata (LHA) with plug-ins to perform behavior analysis using the Labeled Transition System Analyzer (LTSA) or Polyhedral Hybrid Automata Verifier (PHAVer), respectively. The CPS architectural style and analysis plug-ins are illustrated with an example.